2005
DOI: 10.1021/jp052653d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Catalytic Activity of Au3, Au4+, Au5, and Au5- in the Gas-Phase Reaction of H2 and O2 to Form Hydrogen Peroxide:  A Density Functional Theory Investigation

Abstract: We report a detailed density functional theory (B3LYP) analysis of the gas-phase H2O2 formation from H2 and O2 on Au3, Au4+, Au5, and Au5-. We find that H2, which interacts only weakly with the Au clusters, is dissociatively added across the Au-O bond, upon interaction with AunO2. One H atom is captured by the adsorbed O2 to form the hydroperoxy intermediate (OOH), while the other H atom is captured by the Au atom. Once formed, the hydroperoxy intermediate acts as a precursor for the closed-loop catalytic cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
58
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 83 publications
12
58
1
Order By: Relevance
“…One point on which agreement seems to have been reached, is that the main role of gold is the formation of a peroxide species or hydrogen peroxide. This has been confirmed both by experimental and theoretical studies [8,10,[12][13][14]24]. In the model we propose, this is also an essential step, but we also propose another role for gold, namely the activation of propene, which thereafter reacts with titania surface groups [5,19,22] and only in a second step reacts with a peroxide species.…”
Section: Discussionsupporting
confidence: 82%
“…One point on which agreement seems to have been reached, is that the main role of gold is the formation of a peroxide species or hydrogen peroxide. This has been confirmed both by experimental and theoretical studies [8,10,[12][13][14]24]. In the model we propose, this is also an essential step, but we also propose another role for gold, namely the activation of propene, which thereafter reacts with titania surface groups [5,19,22] and only in a second step reacts with a peroxide species.…”
Section: Discussionsupporting
confidence: 82%
“…Naito and Tanimoto [74] have experimentally shown that the hydrogen-deuterium equilibration at 423 K on a 5 wt% Au/SiO 2 catalyst is poisoned by O 2 , but its rate is increased 10 to 30 times on 0.05 wt% Au/SiO 2 catalyst when O 2 is present. The DFT calculations on gas-phase Au 3 clusters are consistent with this observation of facilitated H 2 dissociation in the presence of O 2 [45,46].…”
Section: Introductionsupporting
confidence: 77%
“…We have demonstrated the utility of DFT calculations in our previous work on small unsupported (gas-phase) Au clusters [44][45][46][47][48]. We showed that H 2 and O 2 can react on small Au clusters to form H 2 O 2 [45,46], which may carry out propylene epoxidation on Ti sites in TS-1 [49][50][51][52].…”
Section: Introductionmentioning
confidence: 75%
“…The higher charge transfer is related with a lower ionization potential. It is well known that for Au clusters, the ionization potential values decrease as the number of Au atoms increase in the cluster [57]. According to our results the interaction, measured by the E or H values, is stronger for Au/T than for Au 3 /T even though there is a higher charge transfer for the latter than for the former.…”
Section: Resultssupporting
confidence: 67%